Pengaruh Digital Marketing, Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Produk Hey Jack Original Coffee Kelurahan Merjosari Kecamatan Lowokwaru Kota Malang - Bahri, Syaiful; Rachma, N.; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract In order to escalate customers’ purchase decision, utilizing the appropriate digital marketing strategy as well as maintaining the product’s quality could affect consumers’ purchase decision. This study aims to determine the effect of digital marketing and product quality on consumers' purchase decisions on Hey Jack Original Coffee products in Merjosari village, Lowokwaru sub-district, Malang City. 100 respondents were chose as the sample using Malhotra formula with a purposive sampling method. Multiple linear regression analysis is also used to anaylize the data. The result showed that the effort on utilizing the digital marketing strategy and maintaining the produc quality done by Hey Jack Original Coffee positively and significantly affects its consumers’ purchase decision. Furthermore, suggestion for other businesses is to put more focus on the use of social media in promoting their products in the form of digital marketing and always maintain the quality of their products to avoid disappointing the buyers. Keywords: Digital Marketing, Product Quality, Purchase Decisions.